TRANSAPARANSI ANGGARAN PADA WEBSITE RESMI PEMERINTAH PROVINSI DI INDONESIA - Wahyudin Nor; Lili Safrida; Fahmi Rizani; Diah Fitriaty (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
There is a gap in the practice of budget tranparency through website and themajority of local governments have not optimized the use of Internet technology.The purpose of this paper is to examine the extent to which level of highereducation, internet access in households, local revenue, local expenditure andintergovernmental revenue influence budget transparency on the official website oflocal government. The data of this research comprise 102 budget document duringthe period 2017–2019 collected from 34 local governments across Indonesia byemploying the census method. The data then are analyzed using logistic regression.The results of this study show that level of higher education and internet access inhouseholds has a positive significant influence to budget transparency on localgovernment websites in Indonesia, while the local revenue has a negative nosignificant influence to budget transparency. Local expenditure andintergovernmental revenue has a positive no significant influences to budgettransparency on local government websites in Indonesia.